1
$\begingroup$

I have to compute the following integral:

$$ \lim_{k \rightarrow \infty} \int_{\mathbb{R}^n} \chi_{B_k} f \mathrm{d}\lambda_n(x) $$

$\chi_{B_k}(x) =\begin{cases} 1 &, \text{if } x \in B_k \\ 0 &, \text{otherwise} \end{cases}$, $B_k = \{ x \in \mathbb{R}^n \ | \ \| x \| \le k \}$ and $f \in \mathcal{L}^1 (\mathbb{R}^n)$.

$$f \in \mathcal{L}^1(\mathbb{R}^n) \Leftrightarrow \int_{\mathbb{R}^n} \max\{0,f\} \mathrm{d}\lambda(x) < \infty \text{ and } \int_{\mathbb{R}^n} \max\{0,-f\} \mathrm{d}\lambda(x) < \infty$$

My assumption is that $\lim \limits_{k \rightarrow \infty} \int_{\mathbb{R}^n} \chi_{B_k} f \mathrm{d}\lambda_n(x) = \int_{\mathbb{R}^n} f \mathrm{d}\lambda_n(x)$

But how to show? I tried to use the majorant criterion, but $|f| \in \mathcal{L}^1(\mathbb{R}^n)$ don't have to hold.

I appreciate any hint :) Thank you in advance.

$\endgroup$
  • $\begingroup$ But what are your assumptions on the function $f$? $\endgroup$ – Siminore Aug 15 '14 at 10:00
  • $\begingroup$ $f \in \mathcal{L}^1(\mathbb{R}^n) \Leftrightarrow \int_{\mathbb{R}^n} \max\{0,f\} \mathrm{d}\lambda(x) < \infty$ and $\int_{\mathbb{R}^n} \max\{0,-f\} \mathrm{d}\lambda(x) < \infty$ $\endgroup$ – DerJFK Aug 15 '14 at 10:04
  • $\begingroup$ @Siminore : above you see the definition. I also added it to the post. $\endgroup$ – DerJFK Aug 15 '14 at 10:24
3
$\begingroup$

When $f$ is non-negative, it is a consequence of the monotone convergence theorem.

For the general case, write $f=f^+-f^-$, where $f^+:=\max\{0,f\}$ and $f^-$ are integrable non-negative functions.

$\endgroup$
  • $\begingroup$ Is this right? $$ \lim_{k \rightarrow \infty} \int_{B_k} f_{\pm} \mathrm{d}\lambda(x) = \int_{\mathbb{R}^n} f_{\pm} \mathrm{d}\lambda(x) < \infty$$ $$ \lim_{k \rightarrow \infty} \int_{B_k} f \mathrm{d}\lambda(x) = \lim_{k \rightarrow \infty} \int_{B_k} f_+ \mathrm{d}\lambda(x) - \int_{B_k} f_- \mathrm{d}\lambda(x) = \lim_{k \rightarrow \infty} \int_{B_k} f_+ \mathrm{d}\lambda(x) - \lim_{k \rightarrow \infty} \int_{B_k} f- \mathrm{d}\lambda(x) = \int_{\mathbb{R}^n} f_+ \mathrm{d}\lambda(x) - \int_{\mathbb{R}^n} f_- \mathrm{d}\lambda(x) = ) = \int_{\mathbb{R}^n} f \mathrm{d}\lambda(x) $$ $\endgroup$ – DerJFK Aug 15 '14 at 10:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.